2021
DOI: 10.12688/f1000research.26486.2
|View full text |Cite
|
Sign up to set email alerts
|

Neurons with dendrites can perform linearly separable computations with low resolution synaptic weights

Abstract: In theory, neurons modelled as single layer perceptrons can implement all linearly separable computations. In practice, however, these computations may require arbitrarily precise synaptic weights. This is a strong constraint since both biological neurons and their artificial counterparts have to cope with limited precision. Here, we explore how non-linear processing in dendrites helps overcome this constraint. We start by finding a class of computations which requires increasing precision with the number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The capabilities for discretization in functional networks depend highly on the discretization method (Senn and Fusi, 2005;Gupta et al, 2015;Muller and Indiveri, 2015) and also the neuron models involved. Recently, Cazé and Stimberg (2020) showed that non-linear processing in dendrites enables neurons to perform computations with significantly lower synaptic weight 5 https://www.izhikevich.org/human_brain_simulation/why.htm. resolution than otherwise possible.…”
Section: Discussionmentioning
confidence: 99%
“…The capabilities for discretization in functional networks depend highly on the discretization method (Senn and Fusi, 2005;Gupta et al, 2015;Muller and Indiveri, 2015) and also the neuron models involved. Recently, Cazé and Stimberg (2020) showed that non-linear processing in dendrites enables neurons to perform computations with significantly lower synaptic weight 5 https://www.izhikevich.org/human_brain_simulation/why.htm. resolution than otherwise possible.…”
Section: Discussionmentioning
confidence: 99%
“…The capabilities for discretization in functional networks depend highly on the discretization method (Gupta et al, 2015;Muller and Indiveri, 2015;Senn and Fusi, 2005) and also the neuron models involved. Recently, Cazé and Stimberg (2020) showed that non-linear processing in dendrites enables neurons to perform computations with significantly lower synaptic weight resolution than otherwise possible. Therefore a principled approach to discretization methods and an adequate selection of performance measures are necessary dependent on the respective task.…”
Section: Discussionmentioning
confidence: 99%